Efficiency of five biosolids to supply nitrogen and phosphorus to ryegrass - Corrêa, Rodrigo Studart (Pesquisa Agropecuaria Brasileira, 2004)
Biosolids have been considered satisfactory to supply crops and plant nutrients. The ideal biosolids application rate should result in high crop yields and nutrient uptake, and leave low concentrations of nutrients in soils to avoid environmental problems. The objective of this study was to estimate the capacity of five biosolids to supply N and P to ryegrass (Lolium perenne) after a single application of either fertilizers or biosolids to a Spodosol and an Oxisol. Results showed that 6% – 36% of N and 3% – 7% of P applied as biosolids were recovered in plants grown on the Spodosol, while the range on the Oxisol was 26%–75% for N and 1.2%–3.7% for phosphorus. Biosolids’ efficiency on supplying N and P to plants was similar to fertilizer on the Spodosol, but on the Oxisol it refrained to 65%–67% fertilizer’s efficiency. After a single application of biosolids followed by six consecutive harvests, 25%–94% of the N and 93%–99% of the P were not used by plants and remain in the soils.